TEACHING WRITING OF RECOUNT TEXT BY USING ‘INSIDE OUT’ A FILM BY PETE DOCTER FOR TENTH GRADE STUDENTS OF SMAN N 8 JAMBI ACADEMIC YEAR 2016/2017 - Nevia Hendika; Suyadi Suyadi; Yanti Ismiyati (Universitas Batanghari Jambi, 2018)
This research was done using a film ‘Inside Out’ to developing students writing skills of recount text for the tenth grade students of SMA N 8 Jambi. In order to achieve the objective of this research, the writer designed an experimental research and chose pre-test post-test design with two treatments for this study. the result of the data analysis of the reflection scores for pre-test and post-test showed the increasing mean 52,8 and 73. The finding clearly revealed that a film ‘Inside Out’ as a media was effective enough in helping class X IPA 1 Students of SMAN 8 Jambi to develop recount text writing. Based on the finding, the writer assumes that movie may be used as one of alternative medium in the teaching of recount writing. Keywords: Writing, Recount Text